Epifaniczne przedstawienia Trójcy Świętej na ikonach bizantyjskich i ruskich. Dogmat trynitarny a kanon ikonograficzny. - Cyrek, Olga (Poznańskie Studia Teologiczne, 2011)
The article describes the basic types of pictorial representations of the Holy Trinity. The Old Testament prefiguration of the Trinity that became a type scene is the so-called „Hospitality of Abraham”. This is the variant of the „Trinity” used by Andrew Rublev. The „New Testament Trinity” represents such topics as „Fatherhood” and the „Common Throne”. The revelation of the Trinity as a whole is also evident in icons depicting scenes from Christ’s life, such as the icons of the Nativity, Baptism, Transfiguration on Mount Tabor, where each of the divine persons is manifested in a different way. God the Father is revealed as the sphere of heaven located in the upper part of the image, the Son of God is manifested in human flesh, and the Holy Spirit is depicted in the form of a dove, or a radiant cloud (mandorla). Numerous compositions also make use of the symbol of a triple beam, which stresses the Trinitarian nature of the depicted scene. The formation of epiphanic representations of the Trinity was influenced not only by the realities revealed in the text of the Scripture, but also by the tenets laid down at the Councils of Nicaea in 325 and Constantinople in 381. Trinitarian terminology was also developed by Eastern and Western theologians such as Basil the Great, Greogory of Nazianus, Hilary of Poitiers, Ambrose of Milan, Augustine of Hippo.